Anti-triatomine saliva immunoassays for the evaluation of impregnated netting trials against Chagas disease transmission - Schwarz, Alexandra; Juarez, Jenny Ancca; Richards, Jean; Rath, Bruno; Machaca, Victor Quispe; Castro, Yagahira E; Málaga, Edith S; Levy, Katelyn; Gilman, Robert H; Bern, Caryn; Verastegui, Manuela; Levy, Michael Z (International journal for parasitology, 2011)
Insecticide-impregnated nets can kill triatomine bugs, but it remains unclear whether they can protect against Chagas disease transmission. In a field trial in Quequeña, Peru, sentinel guinea pigs placed in intervention enclosures covered by deltamethrin-treated nets showed significantly lower antibody responses to saliva of Triatoma infestans compared with animals placed in pre-existing control enclosures. Our results strongly suggest that insecticide-treated nets prevent triatomine bites and can thereby protect against infection with Trypanosoma cruzi. Anti-salivary immunoassays are powerful new tools to evaluate intervention strategies against Chagas disease.
Keywords: parazitologie; Insect Control; imunoanalýza; Saliva; Guinea Pigs; Immunoassay; Triatoma; mužské pohlaví; sítě nad lůžka napuštěné insekticidy; morčata; sliny; ženské pohlaví; zvířata; Parasitology; Insect Bites and Stings; kousnutí a bodnutí hmyzem; Peru; Chagas Disease; Insecticide-Treated Bednets; Chagasova nemoc; Female; dezinsekce; Male; Animals